Polityczne konsekwencje spotkań ambasadora Waltera B. Smitha z Wiaczesławem Mołotowem 4 i 9 maja 1948 roku - Wasiewicz, Magdalena (Acta Universitatis Lodziensis. Folia Historica, 2008)
The article presents the activity of the US Ambassador to Soviet Union W. B. Smith during the international tensions of 1948. The Communist takeover in Czechoslovakia was the first and most consequential of the chain of events that occurred in the early months of 1948. The Czech coup catalyzed diplomatic developments in western Europe. On 17 March Britain, France, Belgium, the Netherlands and Luxembourg signed the Brussels Pact. The Truman administration was much more concerned about developments in Eastern Europe. Secretary of State Marshall instructed Ambassador Smith to arrange a meeting with Foreign Minister Molotov to inform him about American foreign policy objectives. Smith was instructed to warn the Soviet minister against any acts of agression and to assure him the United States had no hostile intension against the Soviet Union. On 4 May Ambassador Smith met with Molotov to discuss Soviet-Amcrican relations. Ambassador Smith said American policies were basically defensive, were supported by American people, and did not threaten the Soviet Union. On 9 May Foreign Minister Molotov responded to the 4 May statesment of Ambassador Smith. Molotov denied the charges made by American Ambassador. He accused the United States of being responsible for Soviet-Amcrican tensions. 11 May, Soviet radio and press published the exchange of views between Ambassador Smith and Molotov. American officials assumed the exchange of views would be considered confidcntal. The same day Henry Wallace, the former secretary of commerce in the Truman administration, wrote an open letter to Josef Stalin. Wallace was one of the leaders of the left-wing Democrats. In his letter Wallace called for an end of the cold war. State Department concluded that the actions of the Soviet Union to make public the record of the Smith-Molotov talks and Stalin’s reply to Wallace’s open letter, indicated it was more interested in scoring a propaganda victory than in seriously attempting to resolve Sovict-American differences. Secretary of State Marshall in his speech delivered in Portland, Oregon, criticized the Soviets for making the diplomatic exchange public, without consulting the United States. The Smith-Molotov notes and the Wallace-Stalin correspondence troubled government officials because they threatened to undermine public and congressional support for those policies.